2020
DOI: 10.1210/clinem/dgaa539
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Epinephrine Contributes to the Development of Experimental Hypoglycemia-Associated Autonomic Failure

Abstract: Background Recurrent hypoglycemia blunts counter-regulatory responses to subsequent hypoglycemic episodes, a syndrome known as hypoglycemia-associated autonomic failure (HAAF). Since adrenergic receptor blockade has been reported to prevent HAAF, we investigated whether the hypoglycemia-associated rise in plasma epinephrine contributes to pathophysiology and reported interindividual differences in susceptibility to HAAF. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
1
13
1
Order By: Relevance
“…Importantly, Beverly and colleagues previously showed that release of norepinephrine in the VMH was not impacted by antecedent hypoglycaemia, despite loss of the sympathoadrenal response 12,13 . Taken together, the data suggest that moderate activation of the sympathoadrenal system may be beneficial for the recovery from hypoglycaemia,however, repeated robust activation of the adrenergic system may lead to the development of HAAF as reported by Yimagou and colleagues 8 . This suggests that mild adrenergic blockade may be suitable for preventing the development of HAAF.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…Importantly, Beverly and colleagues previously showed that release of norepinephrine in the VMH was not impacted by antecedent hypoglycaemia, despite loss of the sympathoadrenal response 12,13 . Taken together, the data suggest that moderate activation of the sympathoadrenal system may be beneficial for the recovery from hypoglycaemia,however, repeated robust activation of the adrenergic system may lead to the development of HAAF as reported by Yimagou and colleagues 8 . This suggests that mild adrenergic blockade may be suitable for preventing the development of HAAF.…”
Section: Introductionmentioning
confidence: 52%
“…While numerous mechanisms have been proposed to explain the pathophysiology of HAAF, we and others have shown that repeated activation of the adrenergic system may also contribute to the development of HAAF 4–6 . Both repeated administration of epinephrine to healthy human subjects in the absence of hypoglycaemia and the administration of beta‐adrenergic blockers to type 1 diabetic patients during antecedent episodes of hypoglycaemia have supported this notion 7,8 …”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Years ago, Ramanathan and Cryer [ 5 ] demonstrated that adrenergic blockade with nonselective α- and β-adrenergic antagonists during the first episode of hypoglycemia prevented the expected blunting of the epinephrine response that occurred during a second episode of hypoglycemia, suggesting that the epinephrine released during hypoglycemia may itself be causing impaired awareness of hypoglycemia. More recently, Lontchi-Yimagou and colleagues [ 6 ] demonstrated that healthy volunteers who met the standard criteria for HAAF during the third exposure to hypoglycemia demonstrated higher levels of hypoglycemia-induced epinephrine response during the first exposure to hypoglycemia in our preinduction protocol, although they did find marked interindividual variability in the responses to hypoglycemia. They hypothesized that this variability may explain an individual’s susceptibility to developing impaired awareness.…”
mentioning
confidence: 89%